A antecedent of teacher performance occupational commitment - Özgenel, Mustafa; Özgenel, Mustafa (Kadir Ulusoy, 2019)
The aim of the study is to specify whether the occupational commitment of teachers is a antecedent’s variable that predicts/affects their performance. With this object, relational survey model was used and 535 volunteer teachers from different districts of Istanbul Anatolian Side participated in the study. In this research, data were collected by using Four-Dimensional Occupational Commitment Scale (Blau, 2003) and Teacher Performance Evaluation Scale (Özgenel, 2003). The reliability of the data set was calculated, normal distribution was determined, and parametric tests were performed. According to the findings of the research, the occupational commitment and performance of the teachers were compared according to their gender, educational, seniority, age and school types. A moderate and positive significant relationship was found between teachers' occupational commitment and their performance, and it was found that occupational commitment was a primary variable that predicts/affects teacher performance by 15%. The research findings were discussed in the context of understanding the relationship between teachers' occupational commitment and performance.
Keywords: Commitment; Occupational commitment; Performance